2011
DOI: 10.1371/journal.pone.0016037
|View full text |Cite
|
Sign up to set email alerts
|

Central Angiotensin II Stimulation Promotes β Amyloid Production in Sprague Dawley Rats

Abstract: BackgroundStress and various stress hormones, including catecholamines and glucocorticoids, have recently been implicated in the pathogenesis of Alzheimer's disease (AD), which represents the greatest unresolved medical challenge in neurology. Angiotensin receptor blockers have shown benefits in AD and prone-to-AD animals. However, the mechanisms responsible for their efficacy remain unknown, and no studies have directly addressed the role of central angiotensin II (Ang II), a fundamental stress hormone, in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 89 publications
5
81
1
2
Order By: Relevance
“…24 Also, neither Ang II nor losartan changed CFU-Meg formation in a defined megakaryocyte lineage assay. 24 These data suggest that Ang II facilitates hematopoietic proliferation at an early differentiation an important role of locally produced Ang II, [10][11][12] including a local RAS producing Ang II in bone marrow (BM). 13 Hematopoiesis is carefully controlled.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…24 Also, neither Ang II nor losartan changed CFU-Meg formation in a defined megakaryocyte lineage assay. 24 These data suggest that Ang II facilitates hematopoietic proliferation at an early differentiation an important role of locally produced Ang II, [10][11][12] including a local RAS producing Ang II in bone marrow (BM). 13 Hematopoiesis is carefully controlled.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
“…Importantly, AD patients taking angiotensin receptor blockers were found to have reduced AD-related pathology postmortem [14]. In animal studies, stimulation of the angiotensin system increases leukocyte adhesion, increases permeability of the BBB, induces oxidative stress in the microcirculation of the brain [15], and leads to an increase in A␤ [16] and tau [17] pathologies. Neuronal cell death is also strongly linked to the presence of immunoglobulin G in AD patients' brains.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] In addition, it has been suggested that some ACE inhibitors and ARBs might have benefits not only for the prevention but also for the treatment of mild to moderate Alzheimer disease progression. [27][28][29] Thus the association between an antihypertensive treatment and cognitive function is becoming an important topic. In this trial, we hope to elucidate the relationship between blood pressure or drug combination and cognitive function.…”
Section: Discussionmentioning
confidence: 99%